Keeping the user in mind : instructional design and the modern library - Dent, Valeda Frances; ScienceDirect eBooks (Oxford, UK : Chandos Pub., 2009)
This title provides a down-to-earth look at instructional design and its uses in the academic library, with a particular look at teaching and measuring information literacy skills.
9 Keeping the user in mind: using design thinking to connect libraries and instructional designWhy design?; What is design thinking?; Applying design thinking in your library; Designing better library user experiences; Instructional design: more alike than different; So you want to be a design thinker; References; Further reading; 10 A glimpse of the future: the semantic web and library instructional design; References; Conclusion; Index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Library orientation; Educational technology -- Design; Instructional systems -- Design; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Educational technology -- Design; Instructional systems -- Design; Library orientation; Electronic books